Entrance Skin Dose of Patients Undergoing Chest X-Ray in Selected Hospitals in Jalingo, Taraba State, Nigeria - U, Bawa-Boyi E.; J, John, J.; A, Achimugu; A, Naphtali F. (Darul Yasin Al Sys, 2024)
This study serves as a method of ensuring the quality of radiation exposure by examining the entrance skin doses of patients who undergo Chest X-ray procedures at three prominent diagnostic institutions - Federal Medical Center, Taraba State Specialist Hospital, and Am-Pat Diagnostic Center, all located in Jalingo, Taraba State. Radiation exposure acquired by patients during normal x-rays is known to enhance the risk of cancer. This was the key motivation for this investigation. The Entrance Skin Dose (ESD) for sampled individuals was computed using the 1984 Edmond’s formula. The research utilized a sampling population of 80 patients, divided into 20 samples each machine and subsequently categorized into 10 according to age groups. The average Entrance Skin Dose (ESD) for individuals aged 0-18 years ranged from 0.120 mGy recorded at FMC1 to 0.188 mGy at FMC2. Also the mean ESD for patients in the 19 and above age category had a range from 0.258 mGy at FMC2 to 0.400 mGy at TSSHJ. The Taraba State Specialist Hospital in Jalingo recorded a maximum mean Entrance Skin Dose (ESD) of 0.4mGy for adult patients which surpasses the standard of 0.30 mGy for a year set by the IAEA. From the results obtained, an immediate review of exposure parameters of the FMC2 and TSSHJ is recommended in order to reduce the ESD especially for the adult population so as to reduce the probability of cancer incidence and other radiation-induced side-effects.